Real virtual? : representing architectural time and space - Columbia University (2007)
[Dt.:] Die Website stellt, unter Verwendung multimedialer und virtueller Technologie (z. B. 360° Panoramen in sehr guter Bildqualität, interaktive Pläne), unter anderem einige der bedeutendsten Baudenkmäler der antiken Architekturgeschichte vor. Die Bauten sind in historischer Reihenfolge gegliedert. Unter den aufgenommenen Monumenten sind die Bauten der Akropolis von Athen, Bauten im Gebiet des Forum Romanum und das Pantheon in Rom, außerdem frühchristliche Bauten (z. B. San Vitale, Ravenna), griechische Architektur Siziliens. - [Engl.:] This website offers panoramic views in high resolution and interactive plans of buildings with the aid of multimedia and virtual technology. Inter alia, some of the most important buildings of ancient architecture are presented. The views of the buildings are structured in historical order. There are the monuments of the acropolis at Athens, monuments in the area of the Forum Romanum and the Pantheon in Rome; further buildings of Early Christian period (for ex. San Vitale, Ravenna), Greek architecture of Sicily.